But is it art? : an introduction to art theory - Freeland, Cynthia A. (Oxford University Press, 2001)
"In today's art world many strange, even shocking, things qualify as art. In this book, Cynthia Freeland explains why innovation and controversy are valued in the arts, weaving together philosophy and art theory with many fascinating examples." "She discusses blood, beauty, culture, money, museums, sex, and politics, clarifying contemporary and historical accounts of the nature, function, and interpretation of the arts. Freeland also propels us into the future by surveying cutting-edge web sites, along with the latest research on the brain's role in perceiving art." "This clear, provocative book engages with the big debates surrounding our responses to art and will prove an invaluable introduction to anyone interested in thinking about art."--BOOK JACKET.